Interspecific Competition Reduces Energy Expenditure by Decreasing Intragroup Conflict in a Social Burying Beetle - Bo‐Fei Chen; Yi‐Ching Li; Dustin R. Rubenstein; Angèle Rolland; Syuan‐Jyun Sun; Mark Liu; De‐Pei Chen; Sheng‐Feng Shen (Ecology Letters, 2025)
Assessing the physiological costs of sociality remains challenging due to complex interactions between environmental and social factors. To overcome this challenge, we integrated game theory with empirical research to examine how interspecific competition affects energy expenditure in the cooperatively breeding Asian burying beetle Nicrophorus nepalensis . Our nested tug‐of‐war model made two predictions: beetles facing interspecific competition would experience (1) lower physiological costs due to reduced investment in intragroup conflict, despite increased cooperative effort; and (2) decreasing physiological cost differences between dominance ranks. Using thermal imaging, we analysed body temperature as a proximal indicator of thermogenic effort during carcass work. Results supported our model's two key predictions: beetles competing with blowflies exhibited lower body temperatures, with less pronounced temperature differences between social ranks. Thus, reduced social conflict outweighs the energetic costs of increased cooperation in the face of external threats, providing insights into how environmental conditions shape energy allocation in social species.